2019
DOI: 10.3390/molecules24224118
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Guided Fractionation of Prenylated Benzaldehyde Derivatives as Potent Antimicrobial and Antibiofilm from Ammi majus L. Fruits-Associated Aspergillus amstelodami

Abstract: Ammi majus L.; Family Apiaceae; is a plant indigenous to Egypt. Its fruits contain bioactive compounds such as furanocoumarins and flavonoids of important biological activities. An endophytic fungus was isolated from the fruits and identified as Aspergillus amstelodami (MK215708) by morphology, microscopical characterization, and molecular identification. To our knowledge this is the first time an endophytic fungus has been isolated from the fruits. The antimicrobial activity of the Ammi majus ethanol fruits e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 54 publications
0
20
0
Order By: Relevance
“…Compound 168 showed activity against E. coli, Streptococcus mutans and S. aureus, with MICs of 1.95, 1.95 and 3.9 µg/mL, respectively. The highest antibiofilm activity at concentrataion 7.81 µg/mL against S. aureus and E. coli biofilms, at 15.63 µg/mL concentration against S. mutans and moderate activity (MBIC = 31.25 µg/mL) against P. aeruginosa biofilm was measured [89].…”
Section: Aspergillusmentioning
confidence: 94%
“…Compound 168 showed activity against E. coli, Streptococcus mutans and S. aureus, with MICs of 1.95, 1.95 and 3.9 µg/mL, respectively. The highest antibiofilm activity at concentrataion 7.81 µg/mL against S. aureus and E. coli biofilms, at 15.63 µg/mL concentration against S. mutans and moderate activity (MBIC = 31.25 µg/mL) against P. aeruginosa biofilm was measured [89].…”
Section: Aspergillusmentioning
confidence: 94%
“…The antibacterial activity for the synthesised compounds 5a–m , 9a–c , and 14 was evaluated against bronchitis causing-bacteria; Gram-negative Mycoplasma pneumoniae (ATCC 15531), K. pneumoniae (ATCC 43816), H. influenzae (ATCC 10211), M. catarrhalis (ATCC 25238), B. pertussis (ATCC 9340) and Gram-positive S. pneumoniae (ATCC 1659) using XTT Susceptibility Assay ( Table 2 ) 33 , 34 . The results showed that, most of the evaluated compounds produced a significant antibacterial activity in comparison to the reference drug Azithromycin against the tested bacterial strains.…”
Section: Resultsmentioning
confidence: 99%
“…A colorimetric broth microdilution method was utilised to determine the MIC for the tested hybrids following the XTT [2,3-bis(2-methoxy-4-nitro-5-sulfo-phenyl)-2H-tetrazolium-5-carboxanilide]-reduction assay 33 , 34 . MICs for the tested hybrids was assessed against bacteria causing bronchitis; Gram-negative bacteria: H. influenzae ATCC 10211 , M. pneumoniae ATCC 15531 , K. pneumoniae ATCC 43816, M. catarrhalis ATCC 25238 , and Bordetella pertussis ATCC 9340 , as well as S. pneumoniae ATCC 1659 , representing Gram-positive bacterium, that obtained from the American type culture collection.…”
Section: Methodsmentioning
confidence: 99%
“…The 1 H and 13 C NMR data of 9b ( Table 1 ) were very similar to those of 9c, the only difference in the 13 C NMR spectra was that two methylenes (δ C 24.2, C-8 and δ C 32.2, C-9) in 9c were replaced by a double bond (δ C 120.3, C-8 and δ C 142.9, C-9) in 9b, according with one additional unsaturation and the position of the double bond was determined by analysis COSY and HMBC data. All the spectroscopic information was compared with the literature and the compound was identified as aspergin ( Figure 4 B), also named tetrahydroauroglaucin and dehydroflavoglaucin [ 21 , 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%